Determination of Photoperiod-Sensitive Phase in Chickpea (Cicer arietinum L.) - Daba, Ketema; Warkentin, Thomas D.; Bueckert, Rosalind; Todd, Christopher D.; Tar’an, Bunyamin (Frontiers in Plant Science, 2016)
Photoperiod is one of the major environmental factors determining time to flower initiation and first flower appearance in plants. In chickpea, photoperiod sensitivity, expressed as delayed to flower under short days (SD) as compared to long days (LD), may change with the growth stage of the crop. Photoperiod-sensitive and -insensitive phases were identified by experiments in which individual plants were reciprocally transferred in a time series from LD to SD and vice versa in growth chambers. Eight chickpea accessions with differing degrees of photoperiod sensitivity were grown in two separate chambers, one of which was adjusted to LD (16 h light/8 h dark) and the other adjusted to SD (10 h light/14 h dark), with temperatures of 22/16°C (12 h light/12 h dark) in both chambers. The accessions included day-neutral (ICCV 96029 and FLIP 98-142C), intermediate (ICC 15294, ICC 8621, ILC 1687, and ICC 8855), and photoperiod-sensitive (CDC Corinne and CDC Frontier) responses. Control plants were grown continuously under the respective photoperiods. Reciprocal transfers of plants between the SD and LD photoperiod treatments were made at seven time points after sowing, customized for each accession based on previous data. Photoperiod sensitivity was detected in intermediate and photoperiod-sensitive accessions. For the day-neutral accession, ICCV 96029, there was no significant difference in the number of days to flowering of the plants grown under SD and LD as well as subsequent transfers. In photoperiod-sensitive accessions, three different phenological phases were identified: a photoperiod-insensitive pre-inductive phase, a photoperiod-sensitive inductive phase, and a photoperiod-insensitive post-inductive phase. The photoperiod-sensitive phase extends after flower initiation to full flower development. Results from this research will help to develop cultivars with shorter pre-inductive photoperiod-insensitive and photoperiod-sensitive phases to fit to regions with short growing seasons.